How is the Students Acceptance of Collaborative Writing Tools? The Case of Netboard - Etfita, Fauzul; Wahyuni, Sri; Ilyas, Muhammad; Kumara Walpita Gamage, Chandima; Saranga Sudusinghe, Wasana (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Collaborative learning is an approach to teaching and learning that promotes students’ involvement in a group to solve a problem. This study aims to reveal students’ acceptance of Netboard as an integrated technology tool for a collaborative writing approach, in terms of positive or negative attitudes toward the technology used. To reach the purpose, a quantitative research design was applied with a questionnaire as the main instrument. The researchers collected the data from 58 students in a private university who have experienced the collaborative writing approach in the 2022/2023 academic year. The data was analyzed by calculating the four-point Likert scale and interpreted to find the students’ acceptance. The result of the study indicated a positive attitude toward the utilization of Netboard as a collaborative writing tool. It was described from the affective, behavior, and cognitive aspects. To conclude, integrating a proper technology tool in writing class will be a solution in assisting students’ performance, and this study can be considered as a reference for further research.